2020
DOI: 10.3390/pathogens9080635
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Acquisition of New Delhi Metallo-Beta-Lactamase-Producing Carbapenem-Resistant Enterobacterales (NDM-CRE) among a Cohort of COVID-19 Patients in a Teaching Hospital in Tuscany, Italy

Abstract: We describe the epidemiology of New Delhi Metallo-Beta-Lactamase-Producing Carbapenem-Resistant Enterobacterales (NDM-CRE) colonization/infection in a cohort of COVID-19 patients in an Italian teaching hospital. These patients had an increased risk of NDM-CRE acquisition versus the usual patients (75.9 vs. 25.3 cases/10,000 patient days). The co-infection significantly increased the duration of hospital stay (32.9 vs. 15.8 days).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 5 publications
2
40
1
Order By: Relevance
“…In response to a rapid increase in SARS-CoV-2 infections, many health care facilities adopted mitigation strategies to contend with physical space limitations, constrained availability of personnel, shortages in PPE, and a large number of critically ill patients. Recent single-facility reports from the United States and Europe have described increased acquisition of MDROs among patients hospitalized with COVID-19 ( 6 8 ). Hospital A experienced a large multidrug-resistant CRAB outbreak, primarily involving ICU patients, which extended across multiple units during a surge in COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to a rapid increase in SARS-CoV-2 infections, many health care facilities adopted mitigation strategies to contend with physical space limitations, constrained availability of personnel, shortages in PPE, and a large number of critically ill patients. Recent single-facility reports from the United States and Europe have described increased acquisition of MDROs among patients hospitalized with COVID-19 ( 6 8 ). Hospital A experienced a large multidrug-resistant CRAB outbreak, primarily involving ICU patients, which extended across multiple units during a surge in COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…from specimens collected in February and March harbored an additional carbapenemase gene, encoding New Delhi metallo-β-lactamase (a gene rarely present in CRAB isolates from patients in the United States), indicating that at least one CRAB introduction occurred before the surge of COVID-19 cases(5). Four specimens were nonviable or did not yield CRAB growth.During March-August 2020, hospital A admitted approximately 850 patients with COVID-19.…”
mentioning
confidence: 99%
“…While experts have warned of the link between COVID-19 and AMR [3][4][5][6][7][8], studies report conflicting evidence. Several studies-from, in particular, Germany, Italy and the US-have reported outbreaks or an increase in infections with and/or acquisition of multidrug-resistant bacteria during the COVID-19 pandemic [9][10][11][12]. Further studies have reported cases of antimicrobial-resistant invasive fungal infections in COVID-19 patients [13,14], and one case of azole-resistant Aspergillus spp.…”
mentioning
confidence: 99%
“…The lower incidence is most common among the very early phases of infection as would be anticipated [ 76 , 134 ]. The type of proposed co-pathogen changes during the course of COVID-19 [ 49 , 76 , 118 , 128 , 134 – 140 ]. Common respiratory bacteria more often cause infection in early stages of the illness [ 75 , 125 , 129 , 133 , 141 – 143 ].…”
Section: The Covid-19 Experiencementioning
confidence: 99%